KERANGKA HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL, MANAJEMEN PENGETAHUAN DAN HUMAN CAPITAL - Muhammad Akhsan Tenrisau (AkMen JURNAL ILMIAH, 2017)
With the intention of achieving sustained competitive advantage through developing human capital, organizations focus on developing transformational leaders and employing knowledge management. To take part in this matter, this paper aims to explore leadership and knowledge management literatures to study the interrelationship between transformational leadership, knowledge management, and employee-perceived human capital benefit.